2021
DOI: 10.3390/cancers13020357
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Potentially Avoidable Excess Deaths Associated with Socioeconomic Inequalities in Cancer Survival in Germany

Abstract: Many countries have reported survival inequalities due to regional socioeconomic deprivation. To quantify the potential gain from eliminating cancer survival disadvantages associated with area-based deprivation in Germany, we calculated the number of avoidable excess deaths. We used population-based cancer registry data from 11 of 16 German federal states. Patients aged ≥15 years diagnosed with an invasive malignant tumor between 2008 and 2017 were included. Area-based socioeconomic deprivation was assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…In a recent study by Finke et al, the majority of cancer patients living in the most socioeconomically deprived municipalities were found to have significantly lower survival compared to the most affluent patients in Germany (Finke et al 2021 ). These findings confirm the survival disparity reported in previous studies (Brenner et al 1991 ; Jansen et al 2014 , 2020 , 2021 ). In regard to EC, social deprivation could affect clinical outcomes on several levels from early pathogenesis to stage at diagnosis and treatment.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a recent study by Finke et al, the majority of cancer patients living in the most socioeconomically deprived municipalities were found to have significantly lower survival compared to the most affluent patients in Germany (Finke et al 2021 ). These findings confirm the survival disparity reported in previous studies (Brenner et al 1991 ; Jansen et al 2014 , 2020 , 2021 ). In regard to EC, social deprivation could affect clinical outcomes on several levels from early pathogenesis to stage at diagnosis and treatment.…”
Section: Introductionsupporting
confidence: 92%
“…In Germany however, as of the writing of this paper, we were unable to find studies that dealt with this topic. Jansen et al ( 2021 ) measured the 5-year age standardized relative survival of women diagnosed with Corpus Uteri cancer, among other cancer sites, during the period between 2013 and 2017. The study was based on 200 administrative German districts representing approximately 39% of the entire population.…”
Section: Discussionmentioning
confidence: 99%
“…A number of sociodemographic factors have been associated with variation in outcomes for cancer survivors. Cancer survival is known to vary by socio-economic advantage/disadvantage [6][7][8][9][10][11] with this difference partly explained by variations in stage at diagnosis and treatment differences [6]. Recent evidence suggests that psychosocial factors including living alone, being unmarried and higher levels of depression can also negatively impact survival [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A large study in Germany concluded that compared with other districts, cancer survival was the poorest in the most deprived districts, even after adjustment for cancer stage [23]. Similarly, another study in Germany revealed significantly excess cancer-related avoidable mortality in the more deprived regions [24]. Deprivation was also positively associated with breast cancer survival in England, in which each unit increase in deprivation quintile was associated with an increase in excess mortality [25].…”
Section: Discussionmentioning
confidence: 99%